Oil and gas exploration - edited by Said Gaci; Olga Hachay (John Wiley and Sons, Inc.,American Geophysical Union, 2017)
Oil and Gas Exploration: Methods and Application presents a summary of new results related to oil and gas prospecting that are useful for theoreticians and practical professionals. The study of oil and gas complexes and intrusions occurring in sedimentary basins is crucial for identifying the location of oil and gas fields and for making accurate predictions on oil findings